Frequency upconversion luminescence from Yb+3-Tm+3 codoped PbO-GeO2 glasses containing silver nanoparticles - Assumpcao, Thiago A. A.; da Silva, Davinson M.; Kassab, Luciana R. P. [UNESP]; de Araujo, Cid B. (American Institute of Physics (AIP), 2009)
Infrared-to-visible and infrared-to-infrared frequency upconversion processes in Yb3+-Tm3+ doped PbO-GeO2 glasses containing silver nanoparticles (NPs) were investigated. The experiments were performed by exciting the samples with a diode laser operating at 980 nm (in resonance with the Yb3+ transition F-2(7/2)-> F-2(5/2)) and observing the photoluminescence (PL) in the visible and infrared regions due to energy transfer from Yb3+ to Tm3+ ions followed by excited state absorption in the Tm3+ ions. The intensified local field in the vicinity of the metallic NPs contributes for enhancement in the PL intensity at 480 nm (Tm3+ :(1)G(4)-> H-3(6)) and at 800 nm (Tm3+ : H-3(4) -> H-3(6)). (C) 2009 American Institute of Physics. [doi:10.1063/1.3211300]